Identificação de oportunidades de Produção Mais Limpa em uma cooperativa de reciclagem de plásticos na cidade de Sorocaba-SP - Santos, Fábio Ferreira (2017)
Waste generation is a global challenge to be faced, especially in industrializing countries such as Brazil, where high waste generation in line with structural problems and inadequate waste management can result in environmental, economic and social problems. Thus, recycling can be considered as an important strategy to face this challenge in order to develop practices focused on the triple bottom line (sustainability). The recycling chain in Brazil is considered complex involving multiple actors, among them we can highlight the activities of scavengers as fundamental agents on viability of recycling. However, the scavengers are not always recognized, they are the ones that benefit least in the chain and they face several difficulties. In seeking to overcome the difficulties and achieve better positioning in the chain, scavengers have organized into cooperatives, networks and materials processing centers. From the environmental point of view, recycling processes, especially of post-consumer plastics, can also have an impact on the environment, if management is not established from the collection until the final disposal of the same. It is therefore important to adopt environmental management tools such as Cleaner Production (CP), for example, that result in benefits to the environment, society and organizations. This research aimed to identify opportunities for improvement in plastics recycling process in a cooperative of Sorocaba-SP, through the use of the CP tool. The research consisted of a case study in a cooperative that performs the recycling process of Polyethylene (PE) and Polypropylene (PP), transforming them into flakes and / or pellets. The steps of the CP adopted in this research were based on the Centro Nacional de Tecnologias Limpas (CNTL, 2003) and complemented by SEBRAE guidelines (2005) and by the study of Silva et al. (2013). The following steps were carried out: awareness and general characterization of the cooperative, mapping of the recycling process, quantification of input and output streams, definition of indicators, selection of the evaluation focus, identification of causes of waste generation, effluents and emissions, and identification of CP opportunities. The study revealed that the recycling process of the cooperative is passive to generate environmental impacts, mainly due to the lack of standardization of the raw material and the high consumption of water in the washing stage and consequent generation of effluents. 25 improvement opportunities were identified, focusing mainly on level 1 of housekeeping. In addition, barriers to CP in the cooperative were identified, especially those related to financial issues and lack of government support. Thus, it is necessary to overcome these barriers to an effective implementation of the CP and obtain the consequent economic, environmental and social benefits.